Histological Studies on the Liver of Barbari Goat (Capra hircus) - Nimgaonkar, Mayur Sudhirrao; Singh, Krishna Nand; Kumar, Mukesh; Gond , Surya Pratap (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was conducted on the liver of 6 healthy adult Barbari goats of either sex between the age of 1.5 to 3 years. All the  samples were collected from local slaughter units of Ayodhya district, Uttar Pradesh. The liver of Barbari goat was covered with the  connective tissue capsule called Glisson’s capsule. Capsule was mainly made up of collagen fibers, while reticular fibers were mainly  present in stroma of the organ. One cell thick hepatocyte chords framework was found between the peripheral portal veins and central  vein which formed the hepatic lobule. Portal triad was formed by hepatic artery, portal vein and bile duct situated at the periphery of  lobule. Between the hepatic chords hepatic sinusoids were found. Along with hepatocytes Kupffer cells were also present, which were  the non-parenchymal cells having a large nucleus and pink cytoplasm. Few bundles of collagen fibers were found in the hepatic lobules  & discontinuous endothelium of sinusoids was found.
Keywords: Barbari Goat; Histology; Liver